2015
DOI: 10.1038/nm0515-537a
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Corrigendum: PAI-1 mediates the antiangiogenic and profibrinolytic effects of 16K prolactin

Abstract: In the version of the cover caption initially published, the definitions of the green and blue staining were reversed. Green represents nuclear staining, and blue represents the apical membrane. The error has been corrected in the HTML version of the caption. CO R R I G E N DA A N D E R R ATANATURE MEDICINE VOLUME 21 | NUMBER 5 | MAY 2015 537

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…16-kDa Prolactin fragment also triggers endothelial and cardiomyocyte damage. It induces endothelial cells to package microRNA specifically, miR-146a into exosomes, which are then secreted and taken up by the cardiomyocytes, thereby promoting cardiomyocyte apoptosis by suppressing the neuregulin/ErbB pathway [ 17 , 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…16-kDa Prolactin fragment also triggers endothelial and cardiomyocyte damage. It induces endothelial cells to package microRNA specifically, miR-146a into exosomes, which are then secreted and taken up by the cardiomyocytes, thereby promoting cardiomyocyte apoptosis by suppressing the neuregulin/ErbB pathway [ 17 , 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…As such, the vasculotoxic hormonal changes that occur during and after parturition act as a trigger for PPCM. Indeed, several studies have demonstrated that PPCM is triggered by the rapidly changing environment of late gestation thus inducing vasculopathy in susceptible women ( 13 , 27 , 28 ). This is supported by the fact that hormones that likely trigger PPCM (PRL and sFlt1) are mostly at their peak in late pregnancy and postpartum.…”
Section: Cardiac Mechanical Stress During Pregnancymentioning
confidence: 99%